Arch-manual - Lan, Bruce Q. (Hong Kong Phoenix publishing limited, 2011)
Arch-Manual 4 is the updated edition of Arch-Manual 3, which is devoted to global projects that promote sustainability, make creative use of ecological constraints and requirements, as well as further the development of new urban spaces and processes. It has been conceived as a case study manual that provides an incisive analysis of works by 45 established and rapidly emerging architectural practices. Each project is treated in between four and ten pages and is detailed through color photographs, models, plans, diagrams and a short introductory text. Edited by Bruce Q. Lan, its featured architects mainly include ACXT - IDOM, AIR, AllesWirdGut, archi5, Architects Collective, Arquitectos Anonimos(r), ARTEC Architekten, ARX Portugal Arquitectos, b720 Arquitectos - Fermin Vazquez, Barkow Leibinger Architects, Bevk Perovic, Boltshauser Architekten, Caramel Architekten, CC Arquitectos, Correia & Ragazzi Arquitectos, David Tajchman, and so on.
Keywords: ARCHITECTURE GENERAL (AR-GEN)